Impacto da qualidade de vida no trabalho e da percepção dos valores organizacionais sobre a confiança organizacional - Silva, Uanisléia Lima da (2014)
The studies of employee-organization relationships are favored by the understanding that human resources are a key part of the organizational process. Trust is an important aspect in this process and may influence the effectiveness and organizational performance. Thus, this study aimed to verify the predictive power of perceived organizational values and quality of work life (QWL) on employee confidence in the organization. The sample consisted of 188 formally employed individuals who responded reliable and valid instruments for the constructs investigated. Data were analyzed using descriptive statistics, t test and analysis of standard multiple regression. The results showed that the scales presented suitable reliability índices for the study sample. Regression analyzes indicated that organizational values and QWL factors were significant predictors of organizational competence and ethical components. Opportunism was explained only by domain, prestige and collective values. Note that the values, as well as factors of QWL, contributed differently in explaining the criterion variables. The percentage of variance explained suggest the need to expand the research model of the employee\'s trust antecedents in organization to better understand the formation of this bond.